Tantangan Dan Peluang Eksistensi Asuransi Syariah Pada Era Digital Dan Upaya Pengembangannya Di Indonesia - Wendy Dika Ariani; Fairuz Sabiq (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research aims to analyze challenges and opportunities of sharia insurance in the digital era as well as efforts to develop sharia insurance in Indonesia. This research uses descriptive analysis with a qualitative approach. The discussion in this article is a literature review based on literature references. The results show that based on the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) Number 21/DSN-MUI/IV/2001 sharia insurance is an effort to mutually protect and help a number of people through investment in the form of assets which provides return patterns to face certain risks through sharia-compliant contracts. The development of sharia insurance in Indonesia is quite good and significant with the use of sharia fintech digital technology. With this digital business, the opportunity to reach the wider community becomes easier. However, the challenge is that public knowledge in operating sharia fintech is still minimal. As an effort to develop it, all parties must work hard to introduce and socialize the sharia insurance system in Indonesia by educating the public in operating sharia fintech.